2012
DOI: 10.1371/journal.pone.0049865
|View full text |Cite
|
Sign up to set email alerts
|

An Attempt at a Molecular Prediction of Metastasis in Patients with Primary Cutaneous Melanoma

Abstract: BackgroundCurrent prognostic clinical and morphological parameters are insufficient to accurately predict metastasis in individual melanoma patients. Several studies have described gene expression signatures to predict survival or metastasis of primary melanoma patients, however the reproducibility among these studies is disappointingly low.Methodology/Principal FindingsWe followed extended REMARK/Gould Rothberg criteria to identify gene sets predictive for metastasis in patients with primary cutaneous melanom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…MTSS1 combines protumorigenic and proinvasive activities in melanocytic cells and thus seems to belong to the recently described group of oncogenic metastasis drivers in melanoma 28 . Consistent with the hypothesis that this kind of biological information can inherently be carried already in the genome of early-stage melanomas 28,47,48 , we observed an outlier expression pattern of MTSS1 to coincide with the presence of a copy number alteration at 8q24.13 in a subgroup of primary melanoma samples. The 8q24.13 gene locus seems to carry a certain degree of susceptibility to genetic alterations as it has been identified as a papillomavirus integration site in cervical carcinoma 49 , a translocation site in patients with genetic disorders such as the 22q11.21 deletion syndrome 50 and a site of copy number gain in cancers of prostate 51 , gastroesophageal junction 52 and breast 53 .…”
Section: Discussionsupporting
confidence: 88%
“…MTSS1 combines protumorigenic and proinvasive activities in melanocytic cells and thus seems to belong to the recently described group of oncogenic metastasis drivers in melanoma 28 . Consistent with the hypothesis that this kind of biological information can inherently be carried already in the genome of early-stage melanomas 28,47,48 , we observed an outlier expression pattern of MTSS1 to coincide with the presence of a copy number alteration at 8q24.13 in a subgroup of primary melanoma samples. The 8q24.13 gene locus seems to carry a certain degree of susceptibility to genetic alterations as it has been identified as a papillomavirus integration site in cervical carcinoma 49 , a translocation site in patients with genetic disorders such as the 22q11.21 deletion syndrome 50 and a site of copy number gain in cancers of prostate 51 , gastroesophageal junction 52 and breast 53 .…”
Section: Discussionsupporting
confidence: 88%
“…No reported genes overlap in more than two studies. Of the 50 genes reported in Gschaider et al [60], 7 genes overlap with Winnepenninckx et al [55], though, interestingly, the cellular source of these RNAs is likely to be keratinocytes, endothelial cells, or infiltrating immune cells, which would support that microenvironment and/or host response are key prognostic markers for patient outcomes in primary cutaneous melanoma (Supplementary Table 1). Five genes from a combined list from Conway et al and Jewell et al overlap with Winnepenninckx et al, and osteopontin overlapped between the Conway/Jewell and Gschaider et al studies.…”
Section: Expression Of Protein-coding Genesmentioning
confidence: 90%
“…Our group reported 18 miRNA associated with post-recurrence survival [74], with a subset of 6 of these microRNA ( mir-150, mir-342-3p, mir-455-3p, mir-145, mir-155 , and mir-497 ) defined as a post-recurrence survival signature. Interestingly, miR-342-3p is located in an intron of its host gene EVL , which was recently reported to be associated with metastatic risk in primary melanoma [60]. A recent study replicated the prognostic importance of miR-150 and miR-142 (from the 18 associated with post-recurrence survival [74]) in stage III lymph node metastases and patient sera [75].…”
Section: Expression Of Micrornamentioning
confidence: 97%
See 1 more Smart Citation
“…5 Recently, induced pluripotent cancer cells (iPCCs) were established and it was shown that these cells have a higher resistance toward the MAP kinase pathway inhibitors vem and trametinib. 14 CD24 is frequently overexpressed in human carcinomas 14,15 and malignant melanomas 16,17 and its expression is generally associated with a poor prognosis. Since SOX2, one of the factors used to reprogram cancer cells toward iPCCs, favors a more undifferentiated phenotype, 7 which has been shown to be associated with adaptive resistance, 8,9 SOX2 might play an important role in adaptive resistance.…”
mentioning
confidence: 99%